Answer to Question #208055 in Differential Equations for Adarsh Patel

Question #208055

Solve xd^2y/dx^2-(2x-1)dy/dx+(x-1)y=0


1
Expert's answer
2021-06-18T12:40:49-0400

"x\\frac{d^2y}{dx^2}-(2x-1)\\frac{dy}{dx}\n+(x-1)y=0\\\\\n\\frac{d^2y}{dx^2}-(2-\\frac{1}{x})\\frac{dy}{dx}+(1-\\frac{1}{x})y=0\\\\\nHere, p=-2+\\frac{1}{x}, q=1-\\frac{1}{x}\\\\\nThen,\\\\\n1+p+q=0 \\implies y_1=e^x \\, \\text{is a solution of given differential equation.}\\\\\n\\text{\nNow, put} \\,y=vy_1=ve^x, \\\\ \\text{\nand corresponding }\\,y' and \\,y'' \\text{\nvalues in the given differential equation, we get}\\\\\n\\frac{d^2v}{dx^2}+{1}{x}\\frac{dv}{dx}=0\\\\\nPut\\\\\n u=\\frac{dv}{dx}.\\\\\\text{\nTherefore, the above differential equation is} \\,\n\\frac{du}{dx}+\\frac{u}{x}=0\\\\\\text{\nUsing method of separation of variables},\\\\\n\\frac{du}{u}=-\\frac{dx}{x}\\\\\nlogu=-logx+logc_1\\\\\nu=\\frac{c_1}{x}\\\\\n\\frac{dv}{dx}=\\frac{c_1}{x}\\\\\nv=c_1logx+c_2\\\\\nye^{-x}=c_1logx+c_2\\\\\ny(x)=e^{x}(c_1logx+c_2)\\\\\n\\text{This is the required solution.}"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog